THE SIZE AND CONCENTRATIONAL DEPENDENSE OF THE SURFACE ENERGY OF THIN FILMS OF THE TRANSITIONAL METAL ALLOYS - L.P. Aref`eva; I.G. Shebzukhova (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2016)
On the bases of thermodynamic model we have obtained the ratio for the bond energy of alloy crystals. The modified electron-statistical method has reproduced size and concentration dependences of the surface energy of thin films of the transitional metal alloys.